Mineralogical Analysis of Primary and Secondary Source Sediments to Linnévatnet, Spitsbergen, Svalbard - Perreault, Lauren (2009)
Lauren's project focused on discerning the sources of sediment (using geochemistry) entering Lake Linne' from the surrounding drainage basin including the main meltwater inflow, the surrounding hillslopes and reworked marine muds